Assessing racial differences in lifetime and current smoking status & menthol consumption among Latinos in a nationally representative sample. Issue 5 (3rd July 2020) - Cuevas, Adolfo G.; Ortiz, Kasim; Lopez, Nancy; Williams, David R.
ABSTRACT: Objective: To examine the relationship between race and smoking behaviors among Latinos/Hispanics. Design: Using data from the National Adult Tobacco Survey (NATS), we implemented Log-Poisson regression models for each dependent variable (smoking pattern and menthol cigarette use). Each analysis adjusted for age, gender, marital status, employment status, and socioeconomic status (SES). Final pooled cross-sectional sample included 505 Black-Latinos and 9078 White-Latinos. Results: While no racial differences were found in lifetime smoking status among Latinos, Black-Latinos had a 16.6% (95% CI: 0.274, 0.057) increased risk of menthol smoking compared to White-Latinos. Conclusions: The results indicate that menthol consumption is influenced by race among Hispanics/Latinos. To comprehensively address racial disparities among Latinos/Hispanics, further attention needs to be given to racial differences in smoking-related risks among Latinos/Hispanics.